2008
DOI: 10.1534/genetics.108.088435
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Drosophila neuralized on Complex Behaviors and Brain Structure

Abstract: Understanding how genotypic variation influences variation in brain structures and behavioral phenotypes represents a central challenge in behavioral genetics. In Drosophila melanogaster, the neuralized (neur) gene plays a key role in development of the nervous system. Different P-element insertional mutations of neur allow the development of viable and fertile adults with profoundly altered behavioral phenotypes that depend on the exact location of the inserted P element. The neur mutants exhibit reduced resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…Only three of these genes (Beadex, Sema-5c, and neur) had previously been documented to affect locomotion (19)(20)(21). Many of these candidate genes affect nervous system development and function, as well as other aspects of development, the cell cycle, and oogenesis and spermatogenesis, consistent with previous observations that genes affecting startle-induced locomotion are highly pleiotropic (5,11,12).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Only three of these genes (Beadex, Sema-5c, and neur) had previously been documented to affect locomotion (19)(20)(21). Many of these candidate genes affect nervous system development and function, as well as other aspects of development, the cell cycle, and oogenesis and spermatogenesis, consistent with previous observations that genes affecting startle-induced locomotion are highly pleiotropic (5,11,12).…”
supporting
confidence: 84%
“…Previous studies also suggested that a high fraction of the genome is associated with startle-induced locomotion (5). Only three of the candidate genes affecting startle-induced locomotion had been previously linked to effects on locomotor behavior (19)(20)(21). Although many of the candidate genes affect nervous system development and function, others are in known genes that have not been found to affect locomotion, or indeed any behavior, in computationally predicted genes or in regions of the genome with no nearby annotated gene.…”
Section: A Large Fraction Of the Genome Is Associated With Startle-inmentioning
confidence: 99%
“…These problems can be circumvented by assessing epistatic and pleiotropic effects of single mutations in a common homozygous background. In Drosophila melanogaster, diallel crosses among all mutant alleles affecting the same trait have revealed extensive epistasis (7)(8)(9)(10), whereas studies assessing the same mutations for multiple quantitative traits, including genome-wide variation in gene expression, have shown that pleiotropy is pervasive (10)(11)(12)(13). However, pleiotropic effects of epistatic interactions have not been well-explored.…”
mentioning
confidence: 99%
“…However, pleiotropic effects of epistatic interactions have not been well-explored. Here, we assess the contribution of epistasis and pleiotropy to the genetic architecture of aggression in Drosophila in a diallel cross among P-element mutations associated with hyperaggressive behavior (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation